PP.25.18: COMPARISON OF INCIDENCE OF CONTRAST-INDUCED ACUTE KIDNEY INJURY IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION DEPENDING ON DEFINITIONS. (June 2015) - Gaskina, A.; Lukina, O.; Villevalde, S.; Kobalava, Z.
Abstract : Objective: Contrast-induced acute kidney injury (CI-AKI) is a serious potentially preventable complication of percutaneous coronary interventions (PCI). It remains a challenge as use of PCI is growing, patient population is aging, diabetes and chronic kidney disease are coming more common. The incidence of CI-AKI are not well defined. The aim of the study was to evaluate the incidence of CI-AKI in patients undergoing PCI using different definitions. Design and method: 502 patients (346 male, 64 ± 12 years (M ± SD), arterial hypertension 92%, previous myocardial infarction 38%, diabetes mellitus (DM) 22%, known chronic kidney disease 19%, anemia 16%, heart failure 62%, left ventricular ejection fraction 40 ± 16%) who underwent PCI (stable angina pectoris (SAP), n = 50; unstable AP/non-ST-segment elevation myocardial infarction (UAP/NSTEMI), n = 236; STEMI, n = 216) were examined. CI-AKI was assessed according KDIGO 2012 Guidelines and previously the most frequently used definition (25% increase of serum creatinine (SCr) from baseline or 0.5 mg/dl increase in absolute value within 48–72 hours of contrast administration. Mann-Whitney test was performed. P < 0.05 was considered statistically significant. Results: According KDIGO 2012 definition incidence of CI-AKI was 18 %, in SAP patients 12%; UAP/NSTEMI, 15%; STEMI, 20%, P < 0.01. According previously used definition incidence of CI-AKI was: total population 20%, SAP, 16%; UAP/NSTEMI, 16%; STEMI, 18%, P < 0.01. Conclusions: The highest incidence of CI-AKI both on the 2012 KDIGO Guidelines and earlier version was highest among the STEMI patients with primary PCI.